Care dependency in individuals with chronic physical disease: Its relationship with compliance to treatment and life satisfaction (Annals of Medical Research, 2021)
Aim: The reasons such as the fact that individuals with chronic diseases are mostly in the old age and that the diseases lead to changes in physical and psychological fields may bring about an increase of dependence in meeting daily needs. This study aims to determine the relationship between care dependency and compliance to treatment and life satisfaction in individuals with chronic physical diseases.Material and methods: This research designed as a descriptive and relationship-seeking style includes 294 individuals with chronic physical diseases who were hospitalized for internal medicine clinics of a university hospital. After the ethics committee permission, the data were obtained by patient identification form, Care Dependency Scale, Modified Morisky Scale and Life Satisfaction Scale.Results: It was found out that the level of care dependency and motivation and knowledge levels of the individuals were positively weak (p0.05), and that there was a positive moderate relationship between care dependency and life satisfaction level (p0.01). In addition, individuals’ life satisfaction and motivation level in drug use account for 23% of the total variance in care dependence. In addition, 23% of the change in individuals’ dependency on care results from life satisfaction and motivation for medication use.Conclusions: As the levels of independence increases in fulfilling the care requirements of individuals with chronic physical disease, their compliance with drug and life satisfaction also tend to increase. Moreover, compliance to treatment and the life satisfaction of individuals are also important determinants in care dependency.
Keywords: Care dependency; chronic disease; compliance to treatment; life satisfaction